The C-Terminal Domain of Y-Box Binding Protein 1 Exhibits Structure-Specific Binding to Poly(ADP-Ribose), Which Regulates PARP1 Activity - Naumenko, Konstantin N.; Sukhanova, Mariya V.; Hamon, Loic; Kurgina, Tatyana A.; Anarbaev, Rashid O.; Mangerich, Aswin; Pastré, David; Lavrik, Olga I. (Frontiers in Cell and Developmental Biology, 2022)
Y-box-binding protein 1 (YB-1) is a multifunctional protein involved in the regulation of gene expression. Recent studies showed that in addition to its role in the metabolism of DNA and RNA, YB-1 is involved in the regulation of PARP1 activity, which catalyzes poly(ADP-ribose) [PAR] synthesis under genotoxic stress through auto-poly(ADP-ribosyl)ation or protein trans-poly(ADP-ribosyl)ation. Nonetheless, the exact mechanism by which YB-1 regulates PAR synthesis remains to be determined. YB-1 contains a disordered Ala/Pro-rich N-terminal domain, a cold shock domain, and an intrinsically disordered C-terminal domain (CTD) carrying four clusters of positively charged amino acid residues. Here, we examined the functional role of the disordered CTD of YB-1 in PAR binding and in the regulation of PARP1-driven PAR synthesis in vitro. We demonstrated that the rate of PARP1-dependent synthesis of PAR is higher in the presence of YB-1 and is tightly controlled by the interaction between YB-1 CTD and PAR. Moreover, YB-1 acts as an effective cofactor in the PAR synthesis catalyzed by the PARP1 point mutants that generate various PAR polymeric structures, namely, short hypo- or hyperbranched polymers. We showed that either a decrease in chain length or an increase in branching frequency of PAR affect its binding affinity for YB-1 and YB-1–mediated stimulation of PARP1 enzymatic activity. These results provide important insight into the mechanism underlying the regulation of PARP1 activity by PAR-binding proteins containing disordered regions with clusters of positively charged amino acid residues, suggesting that YB-1 CTD-like domains may be considered PAR "readers" just as other known PAR-binding modules.